Self-assembly of bis(phthalocyaninato)terbium on metal surfaces. (13th August 2015) - Deng, Zhitao; Rauschenbach, Stephan; Stepanow, Sebastian; Klyatskaya, Svetlana; Ruben, Mario; Kern, Klaus
Abstract: Single-molecule magnets represent the smallest stable magnetic entities available to technology, with promising applications in data storage and quantum computation in sight. Therefore, an interface between devices and single-molecule magnets must be developed, for which the self-assembly behavior at surfaces is highly relevant. The molecular magnet bis(phthalocyaninato)terbium (TbPc2 ) represents a molecular system with interesting magnetic properties. In order to fabricate low dimensional nanostructures based on TbPc2, the self-assembly behavior on Cu(100), Cu(111) and Au(111) substrates is studied in ultra-high vacuum (UHV). On Cu(100), TbPc2 does not aggregate even at high coverage, which yields a good zero-dimensional system. On Cu(111), the TbPc2 molecules self-assemble into ribbon-like islands with a high aspect ratio, or an isotropically growing phase, depending on the coverage. On Au(111), TbPc2 molecules form two-dimensional domains from the initial growth stage and extend to highly ordered films, which cover entire terraces at high coverage. The molecular ordering of TbPc2 can be understood based on the behavior of single Pc adlayers, taking into account the molecular double-decker structure. The freedom in the dihedral angle between top and bottom Pc ligands allows one to optimize the molecular ordering through a flexible conformation.